Parental Stimulation in Gross Motor Development at 3-4 Years Old at KB Aisyiyah 08 Kranji Lamongan - Ishlah, Nisydatul; Hilmi, Muhammad Irfan; Himmah, Irliana Faiqotul (Indonesian Journal of Adult and Community Education, 2024)
The purpose of this study is to describe parental stimulation regarding gross motor development in 3-4-year-old children at PG Aisyiyah 08 Kranji, Lamongan Regency. This research utilizes a qualitative descriptive approach. The location of the study was determined using purposive area sampling, and informants were selected using purposive sampling. Data collection methods included observation, interviews, and documentation. Data validity techniques employed were prolonged engagement, persistent observation, and triangulation. Data analysis involved data reduction, data display, and data verification. Based on the findings, parents of students at PG Aisyiyah 08 Kranji do not specifically organize activities to stimulate their children's gross motor development, but they provide toys that can support it. Some parents accompany their children during play, while others do not. Collaborative participation between parents and teachers occurs through regular meetings initiated by teachers to discuss child development. Students at PG Aisyiyah 08 Kranji are capable of performing locomotor and non-locomotor movements well, though not all of them excel in manipulative movements